Environmental Heavy Metal Contamination from Electronic Waste (E-Waste) Recycling ActivitiesWorldwide: A Systematic Review from 2005 to 2017 - Houessionon, M.G.K.; Ouendo, Edgard-Marius . D.; Bouland, C.; Takyi, S.A.; Kedote, N.M.; Fayomi, B.; Fobil, J.N.; Basu, N. (International Journal of Environmental Research and Public Health, 2021)
The recycling of electronic waste (e-waste) contaminates ecosystems with metals, though a compilation of data from across sites worldwide is lacking, without which evidence-based comparisons and conclusions cannot be realized. As such, here, a systematic review of the literature was conducted to identify peer-reviewed studies concerning e-waste sites (published between 2005 and 2017) that reported on the concentration of heavy metals (Cd, Hg, As, Pb and Cr) in soil, water and sediment. From 3063 papers identified, 59 studies from 11 countries meeting predefined criteria were included. Reported metal concentrations were summarized, and a narrative synthesis was performed. This review summarized 8286 measurements of the aforementioned metals in soils (5836), water (1347) and sediment (1103). More than 70% of the studies were conducted in Asia. In nearly all cases, the average metal concentrations in a particular medium from a given site were above guideline values; suggesting soils, water and sediment at, or near, e-waste recycling sites are contaminated. Across all media, concentrations of Pb were generally highest, followed by Cr, As, Cd and Hg. The synthesized information demonstrates that e-waste sites worldwide are contaminated with metals, that geographic data gaps exist, that the quality of most studies can be improved and that action is needed to help reduce such levels to protect human health and the environment.
Research Article
Keywords: e-waste; heavy metals; soil; water; sediment; environment